Reaction time in taekwondo - Vieten, M.; Scholz, M.; Kilani, H.; Kohloeffel, M. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The purpose of the study was to find out if taekwondo players competing on an international level have faster reactions than recreational taekwondo players or sports students. We measured three different time intervals. The time measurements started with the flashing of a light diode and ended respectively with the first visible movement of the hip, the shoulder or the foot. Differences were found depending on the skill level, age and gender with the taekwondo players competing on an international level showing significant faster reactions.